The comparison between universal soil loss equation (USLE) and revised universal soil loss equation (RUSLE) for annual soil loss estimation at construction site - Noor Alia Atiqah , Ahmad Rohaidi (2012)
Developers and contractors nowadays need to be aware of the extent of soil erosion at construction sites by estimating annual soil loss precisely so Erosion and Sediment Control Plan (ESCP) can be implemented with reasonable cost. Soil erosion at construction site that mainly caused by massive earthworks activities could endanger environment by clogging drains with excessive sediments and conducing flash flood in a long term run. Hence, one of the objectives of this research is to determine a suitable method either by Universal Soil Loss Equation (USLE) or Revised Universal Soil Loss Equation (RUSLE) by comparing the soil loss rates and also differentiate the methods. Simultaneously, a RUSLE software program is developed. The study is conducted by comparing annual soil loss yielded by both USLE and RUSLE on a case study at Universiti Teknologi Mara (UiTM) Jasin, Melaka construction site on a 39.99 hectares land. Rate of soil loss is estimated during earthworks activity which considered being as worst case scenario. Rate of soil loss by USLE is obtained from Environment Impact Assessment (ETA) Report done by Europasia Engineering Sdn. Bhd. while rate of soil loss by RUSLE is calculated using the Erosion and Sediment Control Guideline provided by Department of Environment ('DOE). Therefore, the RUSLE software program developed is used to assist in calculations. Conclusively, RUSLE suits to be practised, in construction industry in order to approximate soil erosion rate.